Anabolic steroid abuse in public safety personnel a forensic manual - Turvey, Brent E.; Crowder, Stan (Elsevier Academic Press, 2015)
Anabolic Steroid Abuse in Public Safety Personnel: A Forensic Manual provides readers with information on both the history and overwhelming evidence relating to steroid abuse in the law enforcement subculture. The text raises awareness regarding the pervasiveness of the problem that has grown into a systemic and nationwide phenomenon, and then addresses the consequences of anabolic steroid abuse on individual health, agency liability, and public safety. Particular attention is paid to forensic issues, including investigative, evidentiary, and legal concerns, facilitating just and lawful outcomes when these crimes are suspected or exposed